Research on Rapidly Shaped Charge Cutting Technology of Aircraft Damaged Thin-Wall Structure - Cui, A.Y.; Hu, F.Y.; Wei, H.K.; Liu, H.D.; Wang, Z.; Dong, X.L. (Проблемы прочности, 2016)
Shaped charge cutting technology has been introduced into the field of aircraft structure repair to rapidly reshape irregular holes in thin-walled structures. In the present research, numerical calculation of the dynamic cutting process by ANSYS and experiments of shaped charge cutting on a 2A12 aluminum alloy plate with 2 mm thickness have been carried out. It was found that fast kerf is smooth, producing a neat edge and good linearity. The incision fracture section is arranged in neat rows on a corrugated strip, and the lines are clear. Otherwise, the lower part is slightly messy without obvious distribution rules. The target plate separation method of cumulative cutting is a kind of “pre-penetration” and “late tear” method. The application of shaped charge cutting technology can aid in repair of aircrafts’ thin-walled structural damage.